The Impact of Macroeconomic Factors on the Performance of the E-Commerce Stock Index in Indonesia - Muh Yusuf; Yousf Bellin Swarli (Saniya Institute, 2026)
The purpose of this research is to see the influence of macroeconomics, namely inflation, exchange rates, and interest rates, on the development of the e-commerce stock price index in Indonesia. The data analysis method used is multiple linear regression, including classical assumption tests. The results of the research state that macroeconomics influences the development of the e-commerce stock price index (BUKA), this is proven by the sig value of 0.593 > 0.05 in a positive direction, for the exchange rate variable it was also found that the results did not have a significant influence on the development of the e-commerce stock price index (BUKA), this is proven by the sig value of 0.225 > 0. 05 in a negative direction. In contrast, for the exchange rate variable, a partial test found that the results had a significant impact on the development of the e-commerce stock price index (BUKA), this is proven by a sig value of 0.001 < 0 .05 with a negative direction for simultaneous testing it was found that the variables inflation, exchange rate and interest rates together had an impact on the development of the e-commerce stock price index (BUKA), this was proven by a sig value of 0.000 < 0.05. The variables inflation, exchange rate, and interest rate influence the evolution of the e-commerce stock price index (BUKA) by 68.6%, while variables outside the observation influence 31.4%.